Does Noninformative Text Affect Investor Behavior?. Issue 1 (29th May 2018) - Anderson, Alyssa G.; Larkin, Yelena
Abstract: This article demonstrates that easily processed texts affect investor trading behavior even in the absence of any informational content. We examine the trading symbols of US firms and find that stocks with clever tickers (those that are actual words in the English language) are more liquid, as measured by higher turnover and trading volume, as well as lower spreads. Furthermore, clever ticker stocks are traded more by uninformed investors and have larger market reactions on earnings announcement days. These results suggest that ticker fluency facilitates trading by improving the firm's visibility among retail investors through attention grabbing and memorization.